Penyuluhan Penanganan Kedaruratan Trauma Gigi Di Masa Pandemik Covid-19 Pada Ibu-Ibu PKK Cideng - Jakarta Pusat - Suwartini Tien; Lestari Sri; Ariwibowo Taufiq; Wirahadikusumah Andy (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2022)
Dental trauma is an injury involving the teeth and/or involving the supporting structures of the teeth. Dental trauma can cause tooth fracture, tooth displacement, tooth loss (avulsion), or damage to supporting tissues (gums and bones). During the Covid-19 Pandemic Period, mothers have more dominant time with their children, so they are expected to provide quick and effective action in dental trauma cases. This community Service Counseling aims to increase knowledge and skills in dealing with dental trauma problems. Counseling was carried out by the Trisakti University Faculty of Dentistry Team to PKK organization in Cideng, Gambir, Central Jakarta on January 5, 2022. Counseling includes the knowledge on handling emergency dental trauma using webinar methode with power point and animated videos. There is a significant difference in the mean percentage of correct answers between the pre-test (54,23 + 16,47) and post-test (68.58 + 11.45) with a significance level of p = 0.013. Thus, it can be concluded that after the Counseling activity, there is an increase in the level of knowledge regarding the handling of emergency dental trauma. Training is needed to improve skills so that trauma emergencies can be handled better